DC‐SIGN mediated internalisation of glycosylated extracellular vesicles from Schistosoma mansoni increases activation of monocyte‐derived dendritic cells. Issue 1 (30th April 2020) - Kuipers, Marije E.; Nolte‐'t Hoen, Esther N.M.; van der Ham, Alwin J.; Ozir‐Fazalalikhan, Arifa; Nguyen, D. Linh; de Korne, Clarize M.; Koning, Roman I.; Tomes, John J.; Hoffmann, Karl F.; Smits, Hermelijn H.; Hokke, Cornelis H.
ABSTRACT: Helminths like Schistosoma mansoni release excretory/secretory (E/S) products that modulate host immunity to enable infection. Extracellular vesicles (EVs) are among these E/S products, yet molecular mechanisms and functionality of S. mansoni EV interaction with host immune cells is unknown. Here we demonstrate that EVs released by S. mansoni schistosomula are internalised by human monocyte‐derived dendritic cells (moDCs). Importantly, we show that this uptake was mainly mediated via DC‐SIGN (CD209). Blocking DC‐SIGN almost completely abrogated EV uptake, while blocking mannose receptor (MR, CD206) or dendritic cell immunoreceptor (DCIR, CLEC4A) had no effect on EV uptake. Mass spectrometric analysis of EV glycans revealed the presence of surface N‐glycans with terminal Galβ1‐4(Fucα1‐3)GlcNAc (LewisX) motifs, and a wide array of fucosylated lipid‐linked glycans, including LewisX, a known ligand for DC‐SIGN. Stimulation of moDCs with schistosomula EVs led to increased expression of costimulatory molecules CD86 and CD80 and regulatory surface marker PD‐L1. Furthermore, schistosomula EVs increased expression of IL‐12 and IL‐10 by moDCs, which was partly dependent on the interaction with DC‐SIGN. These results provide the first evidence that glycosylation of S. mansoni EVs facilitates the interaction with host immune cells and reveals a role for DC‐SIGN and EV‐associated glycoconjugates in parasite‐induced immune modulation.